The Relationship Between Parenting Styles And Personal Hygiene Independence In Preschool Children - Oom Komalasari; Dewi Anggraini; Sihombing, Putriatdah Sarinah (Universitas Yatsi Madani, 2025)
Independence in maintaining personal hygiene is a crucial aspect of preschool children's development. One of the factors influencing this development is the parenting style applied by parents. An appropriate parenting style can help children develop responsibility and independence from an early age. This study aims to determine the relationship between parenting style and independence in personal hygiene among preschool children at Al-Ikhlas Kindergarten, Serpong, South Tangerang, in 2024. This research employed a quantitative approach with a cross-sectional design and utilized Fisher’s Exact test for analysis. A total of 46 respondents were selected using simple random sampling. The results showed that the majority of parents applied a democratic parenting style (27 respondents or 54%), and most children were categorized as independent (31 respondents or 62%). The p-value obtained was 0.003. Therefore, it can be concluded that there is a significant relationship between parenting style and independence in personal hygiene among preschool children at Al-Ikhlas Kindergarten, Serpong, South Tangerang, in 2024